Internalization Of Local Wisdom Values To Support The Policy Of Reducing Stunting In Tinukari Village, North Kolaka Regency - Umbarsari, Dewi (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
This study aims to understand and analyze the role of local wisdom values ​​in supporting stunting reduction policies in rural areas. The research location was in Tinukari Village, Wawo District, North Kolaka Regency. The urgency of this study stems from the phenomenon of stunting cases which are still a national problem, so that it requires serious handling from all levels of government, from the national level to the village government level. The seriousness of the village government in handling stunting must continue to be encouraged in order to welcome the demographic bonus in 2030 and the vision of a golden Indonesia in 2045. In this study, data collection was carried out through interviews and documentation studies. While data analysis was carried out with a three-flow process procedure, namely: data reduction, data presentation, and drawing conclusions. The results of the analysis show that the stunting handling policy carried out by the Tinukari village government is based on input from various elements of society at the stunting discussion event in the village. The stunting discussion activity is one of a series of pre-deliberations at the village level in order to prepare the Tinukari Village Government Work Plan (RKP) every year. The strategies carried out include: (1) encouraging the back to nature movement. This movement is carried out by maximizing the potential of agricultural products owned by Tinukari village. By encouraging residents, especially pregnant and breastfeeding mothers, to consume fresh vegetables from their own gardens; (2) building collaboration and synergy based on local wisdom. The concrete efforts made through this movement are to revive the spirit of